2007
DOI: 10.1140/epjb/e2007-00015-9
|View full text |Cite
|
Sign up to set email alerts
|

Spin-dependent transport in cluster-assembled nanostructures: influence of cluster size and matrix material

Abstract: Abstract. Spin-dependent transport in granular metallic nanostructures has been investigated by means of a thermoelectric measurement. Cobalt clusters of well-defined size ( n = 15 − 600) embedded in copper and silver matrices show magnetic field responses of up to several hundred percent at low temperature. The experimental observations are identified as due to spin mixing. The influence of cluster size and matrix are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…So far it was observed that in crossed-line [CoFe/Bi/Co] trilayers [6][7][8][9][10] the magnetic coupling between the two ferromagnetic layers oscillates as a function of Bi spacer thickness between ferromagnetic and antiferromagnetic couplings whereas [Co/Bi] n thin films may exhibit [10,11] a change of polarity in anomalous Hall effect (AHE) loops. In addition, preliminary DC-magnetoresistance measurements [11] in line structures of [Co(1 nm)/Bi(2.5 nm)] 15 stripes provide evidence for a positive MR effect of 80% at 10 K, which is reminiscent of the magnetothermogalvanic voltage (MTGV) signal [12,13].…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…So far it was observed that in crossed-line [CoFe/Bi/Co] trilayers [6][7][8][9][10] the magnetic coupling between the two ferromagnetic layers oscillates as a function of Bi spacer thickness between ferromagnetic and antiferromagnetic couplings whereas [Co/Bi] n thin films may exhibit [10,11] a change of polarity in anomalous Hall effect (AHE) loops. In addition, preliminary DC-magnetoresistance measurements [11] in line structures of [Co(1 nm)/Bi(2.5 nm)] 15 stripes provide evidence for a positive MR effect of 80% at 10 K, which is reminiscent of the magnetothermogalvanic voltage (MTGV) signal [12,13].…”
Section: Introductionmentioning
confidence: 91%
“…To extract temperature and spin-dependent effects from the dominant part of the resistivity, a specific thermoelectric measurement protocol uses [12] a chopped laser beam that irradiates a film of nanogranular Co embedded in a Cu or Ag matrix, inducing a temperature oscillation of about 1 K at the center of the film (without to induce a net temperature gradient at 14 K). It seems that the MTGV signal is not directly correlated to spin-dependent transport properties like the giant magnetoresistance (GMR) effect observed [15] in films of nanogranular Co embedded in a Cu or Ag matrix. Thus, the detection of the MTGV signal is independent [15] of the nonmagnetic metallic matrix because it detects spin-mixing asymmetries from the local spin polarization of the conduction electrons that precess about the exchange field as they traverse the magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations